15 Minutes: Belarus! - Dashkevich, Aleh; Dashuk, Volha; Dzianowicz, Beata; Kilian, Jolanta; Volakh, Iryna; Zamojski, Jan (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
15 Minutes: Belarus!